Genomic dissection of host–microbe and microbe–microbe interactions for advanced plant breeding. (April 2017) - Kroll, Samuel; Agler, Matthew T; Kemen, Eric
Graphical abstract: Highlights: Sequencing plants and microbiota has identified mechanisms of communal interactions. Identification of host traits, responsible for microbial community structure. Plant microbiota members evolve at multiple speeds and vary in host specificity. Niche formation is involved in the structuring of the host associated microbiome. Niche customization for beneficial microbes is an important plant breeding trait. Abstract : Agriculture faces many emerging challenges to sustainability, including limited nutrient resources, losses from diseases caused by current and emerging pathogens and environmental degradation. Microorganisms have great importance for plant growth and performance, including the potential to increase yields, nutrient uptake and pathogen resistance. An urgent need is therefore to understand and engineer plants and their associated microbial communities. Recent massive genomic sequencing of host plants and associated microbes offers resources to identify novel mechanisms of communal assembly mediated by the host. For example, host–microbe and microbe–microbe interactions are involved in niche formation, thereby contributing to colonization. By leveraging genomic resources, genetic traits underlying those mechanisms will become important resources to design plants selecting and hosting beneficial microbial communities.